Respuesta :
Here, 3x + 2y = 12
2x + 2y = 10
Subtract 2nd from 1st equation,
x = 2
Now, substitute in 2nd,
2(2) + 2y = 10
2y = 10 - 4
y = 6/2
y = 3
In short, Your Answer would be: (2, 3)
Hope this helps!
2x + 2y = 10
Subtract 2nd from 1st equation,
x = 2
Now, substitute in 2nd,
2(2) + 2y = 10
2y = 10 - 4
y = 6/2
y = 3
In short, Your Answer would be: (2, 3)
Hope this helps!
3x + 2y = 12 ----(i)
2x + 2y = 10 ----(ii)
Subtracting (ii) from (i),
x = 2
Now putting the value of x= 2 in (i),
3 x 2 + 2y = 12
6 + 2y = 12
2y = 6
y = 3
The value of x = 2 , y = 3
2x + 2y = 10 ----(ii)
Subtracting (ii) from (i),
x = 2
Now putting the value of x= 2 in (i),
3 x 2 + 2y = 12
6 + 2y = 12
2y = 6
y = 3
The value of x = 2 , y = 3